The role of Ekoxinal in the treatment of infertility - А. М. Феськов; И. М. Безпечная; И. А. Феськова; В. В. Лазуренко (Publishing House TRILIST, 2019)
The effective treatment of infertility and an increase in the effectiveness of ART is a current problem of modern reproductive medicine, and therefore, is the important task is to clarify the possibility of using drugs containing myo-inositol to treat infertility caused by sperm hypomotility. The purpose of study was to define the role of Ecoxinal suppositories in infertility treatment in a natural way. We examined 80 married couples with unexplained infertility, that lasted from 1 to 4 years (main group). The control group consisted of 30 married couples who do not suffer from infertility. The patients of the main group were divided into two clinical groups of 40 women in each group by the randomized method. Patients of the first clinical group tried to get pregnant without taking myo-inositol. Patients of the second clinical group received Ecoxinal (contains 2 mg of myo-inositol) intravaginally in the form of suppositories during the periovulatory period (from 11 to 16 days with a 28-day menstrual cycle) when the diameter of the dominant follicle is more than 16 mm. All female patients were examined and treated on the background of a natural or induced ovulation cycles. As a result of the study, it was found that intravaginal use of Ecoxinal suppositories in fertile women whose husbands suffer from infertility (oligoasthenospermia) significantly increases the pregnancy rate to 22.5%. The conditions for intravaginal use of Epoxial suppositories are passable fallopian tubes with preserved fimbrial sections and spermograms of actively motile spermatozoa of at least 3.7 ± 2.1 million/ml, and in the case of treatment using the swim up method, they should be at least 10 million/ml.